Armenians in the Service of the Ottoman Empire - Krikorian, Mesrob K.
1 online resource (xii, 149 pages)
Keywords: “First published in 1977. Although hundreds of books have been published on the Armenian question and massacres, very little is known about their services in the cultural, economic and administrative life and development of the Ottoman Empire. This study is an investigation into the contribution by Armenians to Ottoman public life from 1860, when the Armenian community in Turkey was given a new legislative Constitution on the basis of Tanzimat (Reforms) until 1908, when the young Turks seized power and there followed a bitterly fanatic policy of intolerance which had tragic consequences for both the Armenians and the Turks. The author has concentrated his investigations on the eastern provinces of Anatolia, which earlier formed the western part of historic Armenia and which in the diplomatic language of the nineteenth century were referred to as provinces inhabited by Armenians. To these he has added the provinces of Syria, close to the neighbouring Armenian Kingdom of Cilicia, and where, especially in and around Aleppo, old Armenian communities had settled. Both in Anatolia and Syria, the Armenians were employed in various administrative, judicial, economic and secretarial fields and, to a lesser extent, in technical affairs, agriculture, education and public health. The author shows how this contribution was made in spite of the fact that for the Armenians these were years of transition from their established status as a favoured Christian millet to the tragic insecurity of a hunted people. “--Provided by publisher.